A cooperative PC/network-processor platform for gigabit traffic generation. (2nd December 2009) - Antichi, Gianni; Di Pietro, Andrea; Ficara, Domenico; Giordano, Stefano; Procissi, Gregorio; Vitucci, Fabio
Evaluating the performance of high-speed networks is a critical task that requires reliable tools to generate traffic workloads at high rates. The current software tools provide poor performance in terms of packets per second and timing/rate accuracy, because of the intrinsic limitations of the PC architecture. This paper proposes a different approach, based on a cooperative PC/NP architecture: an advanced software tool runs on a host PC and instructs the processing engines of an Intel IXP2400 network processor, which take care of the actual traffic generation. This way we keep the high flexibility of PC tools while achieving the high packet rates of hardware solutions. The system is able to generate several traffic models (to date, constant bit rate, Poisson and Poissonian arrival of burst are implemented); however the tool is easily extensible in that any other traffic models can be added through the available APIs. In order to improve the system precision, a time correction mechanism is also introduced. Finally, the capability of manipulating and reproducing an actual trace is provided.